2020
DOI: 10.1080/2326716x.2020.1820406
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and the big five personality traits of counselor educators

Abstract: This study examined the association between Big Five personality and counselor educators' transformational leadership style. Findings indicate that all five personality traits were significant predictors. Transformational leaders were characterized by a low score on Neuroticism and high scores on Extraversion, Openness to Experience, Agreeableness, and Conscientiousnes s. Extraversion, Agreeableness, and Openness to Experience were the strongest predictors. This study did not find gender or racial/ethnic diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…Third, no relationship was found between personality traits of middle-leaders: extraversion, agreeableness, conscientiousness, neuroticism, and openness to experiences and TL. These results are surprising since previous research showed that agreeableness and openness to experience are predictors of TL (Lopez-Perry, 2020). Perhaps, the trait activation theory (Tett and Burnett, 2003) may offer an explanation; traits reflect behavioral tendencies in people, but the expression of these traits in behaviors can also be affected by the situation (Hu and Judge, 2017).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Third, no relationship was found between personality traits of middle-leaders: extraversion, agreeableness, conscientiousness, neuroticism, and openness to experiences and TL. These results are surprising since previous research showed that agreeableness and openness to experience are predictors of TL (Lopez-Perry, 2020). Perhaps, the trait activation theory (Tett and Burnett, 2003) may offer an explanation; traits reflect behavioral tendencies in people, but the expression of these traits in behaviors can also be affected by the situation (Hu and Judge, 2017).…”
Section: Discussioncontrasting
confidence: 69%
“…The focus on both TL and its sub-dimensions leans on current research (Tepper et al, 2018), emphasizing the differential correlation of TL sub-dimensions to employee work-related outcomes. The Big Five typology was proposed as an antecedent to middleleaders' TL because studies have shown that the Big Five dimensions correlate to TL (Lopez-Perry, 2020). Although recent research has shown that leaders' personal traits are critical components in leading a team effectively and promoting employee behaviors (Benoliel, 2017(Benoliel, , 2021bHu and Judge, 2017), few studies in the educational context have focused on the differential impact of the Big Five typology on middle-leaders' tendency toward the sub-dimensions of TL and its implications for teachers ' commitment. This investigation can make several important contributions to the educational research.…”
Section: Introductionmentioning
confidence: 99%
“…Agreeableness Judge & Bono (2000), Phipps & Prieto (2011), Lopez-Perry (2020. Positive Zopiatis & Constanti (2012).…”
Section: Positivementioning
confidence: 99%
“…Positive Zopiatis & Constanti (2012). None Openness Judge & Bono (2000), Phipps & Prieto (2011), Zopiatis & Panayiotis (2012), Magano et al (2020), Lopez-Perry (2020. Positive Neuroticism Phipps & Prieto (2011), Lopez-Perry (2020).…”
Section: Positivementioning
confidence: 99%
“…Transformational leadership is one of the most influential current leadership theories not only in management theory generally (Felfe & Schyns, 2010;Judge & Bono, 2000;Procházka & Vaculík, 2015) but also in education (Dababneh et al, 2021;Kaliská, 2019;Lopez-Perry, 2020;Sollárová et al, 2019). Already Leithwood (1994) has suggested that there is some empirical support for using the transformational leadership model in school restructuring initiatives.…”
mentioning
confidence: 99%